Successful intraprocedural anticoagulation with bivalirudin during pulmonary vein isolation in a patient with known heparin-induced thrombocytopenia type II - Barbara Bellmann, MD (Journal of Arrhythmia, 2016)
We report the case of a 56-year-old female who presented with symptomatic paroxysmal atrial fibrillation. Anamnestic heparin-induced thrombocytopenia (HIT) type II was suspected, and a rapid diagnostic test showed antibodies against platelet factor 4. The heparin-induced platelet activation-assay was negative. Radiofrequency pulmonary vein isolation with intraprocedural anticoagulation using bivalirudin was ultimately performed. Dosing was controlled by monitoring the activated clotting time. Post-procedural blood tests were normal. There were no thromboembolic or bleeding events. Bivalirudin is a therapeutic option for anticoagulation during pulmonary vein isolation procedures in patients with a history of HIT type II.